Mixing Acid Salts and Layered Double Hydroxides in Nanoscale under Solid Condition - Hirokazu Nakayama; Aki Hayashi (MDPI AG, 2014)
The immobilization of potassium sorbate, potassium aspartate and sorbic acid in layered double hydroxide under solid condition was examined. By simply mixing two solids, immobilization of sorbate and aspartate in the interlayer space of nitrate-type layered double hydroxide, so called intercalation reaction, was achieved, and the uptakes, that is, the amount of immobilized salts and the interlayer distances of intercalation compounds were almost the same as those obtained in aqueous solution. However, no intercalation was achieved for sorbic acid. Although intercalation of sorbate and aspartate into chloride-type layered double hydroxide was possible, the uptakes for these intercalation compounds were lower than those obtained using nitrate-type layered double hydroxide. The intercalation under solid condition could be achieved to the same extent as for ion-exchange reaction in aqueous solution, and the reactivity was similar to that observed in aqueous solution. This method will enable the encapsulation of acidic drug in layered double hydroxide as nano level simply by mixing both solids.